Molecular Interactions in Solid Dispersions of Poorly Water-Soluble Drugs - Thao T. D. Tran; Phuong H. L. Tran (MDPI AG, 2020)
Physicochemical characterization is a crucial step for the successful development of solid dispersions, including the determination of drug crystallinity and molecular interactions. Typically, the detection of molecular interactions will assist in the explanation of different drug performances (e.g., dissolution, solubility, stability) in solid dispersions. Various prominent reviews on solid dispersions have been reported recently. However, there is still no overview of recent techniques for evaluating the molecular interactions that occur within solid dispersions of poorly water-soluble drugs. In this review, we aim to overview common methods that have been used for solid dispersions to identify different bond formations and forces via the determination of interaction energy. In addition, a brief background on the important role of molecular interactions will also be described. The summary and discussion of methods used in the determination of molecular interactions will contribute to further developments in solid dispersions, especially for quick and potent drug delivery applications.